The Social Life of Social Death: On Afro-Pessimism and Black Optimism - Sexton, Jared (InTensions, 2011)
In what is his finest role, but also his most distressing, the legendary Sidney Poitier plays one Virgil Tibbs, a Philadelphia police detective in transit from an out-of-state visit to his mother’s residence, in Norman Jewison’s Academy Award-winning 1967 film, In the Heat of the Night. The indomitable Mr. Tibbs has been commandeered by the police chief of Sparta, Mississippi, to solve the murder of Philip Colbert, a Chicago industrialist whose business plan for the development of the local economy has now been jeopardized by his untimely death. Chief Gillespie has justice on his mind, to be sure, but also the rate of unemployment of his rural working-class white constituency. Closing the case to the satisfaction of the industrialist’s widow ensures the job creation essential to the maintenance of law and order on this side of the tracks. Identifying a black perpetrator (I was about to write “suspect” but use of that term would require a presumption of innocence not afforded here) ensures that individualized disorder stays on that side of the tracks. It’s a two-for-one deal that keeps everything on track and, more importantly, keeps in place the tracks themselves: the built environment of segregation and the mythos of Jim Crow.